Market failures and the additionality effects of public support to private R&D: Theory and empirical implications - Tuomas Takalo; Tanja Tanayama; Otto Toivanen (Bank of Finland, 2013)
We extend the theoretical basis of the empirical literature on the effects of R&D subsidies by providing an estimable model of strategic interaction among subsidy applicants, and public and private sector R&D financiers. Our model incorporates fixed R&D costs and a cost of external finance. We derive the optimal support rule. At the intensive (extensive) margin the costs of external funding reduce (increase) the optimal subsidy rate. We also establish necessary and sufficient conditions for the existence of additionality. It turns out that additionality at the intensive margin is less likely with large spillovers. Our results suggest that the relationship between additionality and welfare may not be straightforward.
URN:NBN:fi:bof-20140807448
Keywords: O38; O31; L32; H25; G28; 330; R&D; entrepreneurial finance; R&D subsidies; innovation policy